Nature of M-Ga bonds in dihalogallyl complexes (η5-C5H5)(Me3P)2M(GaX2) (M = Fe, Ru, Os) and (η5-C5H5)(OC)2Fe(GaX2) (X = Cl, Br, I): a DFT study. - Pandey, K; Patidar, P; Aldridge, S (2010)
Density functional theory (DFT) calculations have been performed on the terminal dihalogallyl complexes of iron, ruthenium, and osmium (η(5)-C(5)H(5))(Me(3)P)(2)M(GaX(2)) (M = Fe, Ru, Os; X = Cl, Br, I) and (η(5)-C(5)H(5))(OC)(2)Fe(GaX(2)) (X = Cl, Br, I) at the BP86/TZ2P/ZORA level of theory. On the basis of analyses suggested by Pauling, the M-Ga bonds in all of the dihalogallyl complexes are shorter than M-Ga single bonds; moreover, on going from X = Cl to X = I, the optimized M-Ga bond distances are found to increase. From the perspective of covalent bonding, however, π-symmetry contributions are, in all complexes, significantly smaller than the corresponding σ-bonding contribution, representing only 4-10% of the total orbital interaction. Thus, in these GaX(2) complexes, the gallyl ligand behaves predominantly as a σ donor, and the short M-Ga bond lengths can be attributed to high gallium s-orbital character in the M-Ga σ-bonding orbitals. The natural population analysis (NPA) charge distributions indicate that the group 8 metal atom carries a negative charge (from -1.38 to -1.62) and the gallium atom carries a significant positive charge in all cases (from +0.76 to +1.18). Moreover, the contributions of the electrostatic interaction terms (ΔE(elstat)) are significantly larger in all gallyl complexes than the covalent bonding term (ΔE(orb)); thus, the M-Ga bonds have predominantly ionic character (60-72%). The magnitude of the charge separation is greatest for dichlorogallyl complexes (compared to the corresponding GaBr(2) and GaI(2) systems), leading to a larger attractive ΔE(elstat) term and to M-Ga bonds that are stronger and marginally shorter than in the dibromo and diiodo analogues.